Development and Application of Fiber Optic-Based Thermal Wave Resonant Cavity Technique for Measurement of Thermal Diffusivity of Liquids - Noroozi, Monir (2007)
In the study a thermal wave resonant cavity technique (TWRC) was set up and was used to measure thermal diffusivity of various types of liquids. In this technique the thermal diffusivity was determined by scanning the cavity length, instead of frequency, that has a high signal-to-noise ratio in thermally thick case. By using metal foil that attached to a tube as the thermal wave (TW) generator the calibration of the conventional TWRC set up was done on distilled water and the thermal diffusivity value, i.e. 1.44×10-3 cm2/s, agrees with literature value. Further, a few liquids thermal diffusivity, including crude palm (0.988×10-3 cm2/s), soy bean (1.06×10-3 cm2/s), corn oil (0.934×10-3 cm2/s), were determine by using this set up. In this set up the TW is enough to be regarded as rays reflecting and transmitting in cavity. Later the metalized optical fiber tip was used to generate TW instead of metal foil attached to a tube as in the case of conventional TWRC technique. A polymer optical fiber tip or free end coated with silver conductive paint was used to generate TW, by moving this tip with respect to detector and the liquid thermal diffusivity was obtained in a thermally thick region. The thermal diffusivity of distilled water, glycerol, and five different types of cooking oil used which are sunflower, soy bean, olive, corn and palm oils were determined with four-significant-figure at room temperature. These values are in good agreement to the values reported in literatures. The TW field was calculated in a three-dimensional approach. The calculations show that the dimensionality of the TW field in the cavity depends on the lateral (radial) heat transfer boundary conditions and the relation between the laser beam spot size and TW generator diameter. The three-dimensional treatment of the metalised fiber tip was reduced to one-dimensional treatment by using a relatively bigger TW generator diameter compared to laser beam spot size. The set up using optical fiber end also was used to determine thermal diffusivity of a two-layer which is normally difficult to achieve in the conventional large area metal foil due to contact problem. In order to check the validity of the proposed model, the method was experimentally tested for distilled water and glycerol; the values obtained were close to the literature values. A good linear relation of the amplitude with respect to cavity length in thermally thick region of both media was observed. In other TWRC methods the thermal diffusivity values can be obtained by measuring the relative distance of two adjacent extrema. The thermal diffusivity values were obtained by this method compare with “fitting data” method.